Monocyte/Macrophage Lineage Cells From Fetal Erythromyeloid Progenitors Orchestrate Bone Remodeling and Repair - Yahara, Yasuhito; Ma, Xinyi; Gracia, Liam; Alman, Benjamin A. (Frontiers in Cell and Developmental Biology, 2021)
A third of the population sustains a bone fracture, and the pace of fracture healing slows with age. The slower pace of repair is responsible for the increased morbidity in older individuals who sustain a fracture. Bone healing progresses through overlapping phases, initiated by cells of the monocyte/macrophage lineage. The repair process ends with remodeling. This last phase is controlled by osteoclasts, which are bone-specific multinucleated cells also of the monocyte/macrophage lineage. The slower rate of healing in aging can be rejuvenated by macrophages from young animals, and secreted proteins from macrophage regulate undifferentiated mesenchymal cells to become bone-forming osteoblasts. Macrophages can derive from fetal erythromyeloid progenitors or from adult hematopoietic progenitors. Recent studies show that fetal erythromyeloid progenitors are responsible for the osteoclasts that form the space in bone for hematopoiesis and the fetal osteoclast precursors reside in the spleen postnatally, traveling through the blood to participate in fracture repair. Differences in secreted proteins between macrophages from old and young animals regulate the efficiency of osteoblast differentiation from undifferentiated mesenchymal precursor cells. Interestingly, during the remodeling phase osteoclasts can form from the fusion between monocyte/macrophage lineage cells from the fetal and postnatal precursor populations. Data from single cell RNA sequencing identifies specific markers for populations derived from the different precursor populations, a finding that can be used in future studies. Here, we review the diversity of macrophages and osteoclasts, and discuss recent finding about their developmental origin and functions, which provides novel insights into their roles in bone homeostasis and repair.